A new mute species of the genus Nemobius Serville (Orthoptera, Gryllidae, Nemobiinae) discovered in colluvial, stony debris in the Iberian Peninsula: A biological, phenological and biometric study - Barranco, Pablo; Gilgado, José D.; Ortuño, Vicente M. (Zootaxa, 2013)
Sampling of a Mesovoid Shallow Substratum (MSS) of a scree in the Guadarrama mountains (Madrid, Spain) revealed a population of crickets of the genus Nemobius Serville. A detailed morphological study revealed that the cricket was a new species, Nemobius interstitialis sp. nov., which is principally characterized by the absence of a tympanum in the outer margin of the foreleg tibiae and a peculiar design of venation of the forewing of the male. Sampling of this environment over 1 year using surface and MSS pitfall traps, set at a depth of one meter, allowed study of population dynamics. A pop-ulation maximum is attained in August. Abiotic (temperature and humidity) and biotic (accompanying fauna) data are giv-en to contextualize the habitat of this new species.